PERLINDUNGAN HUKUM TERHADAP NASABAH BANK DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Rumelda Silalahi; Onan Purba (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
In today's modern world, the role of banking in advancing the economy of a country is very large. Almost all sectors that are associated with various financial activities always require bank services. Banking as a financial intermediary institution plays an important role in the national development process. Law Number 8 of 1999 concerning Consumer Protection is also closely related, particularly in terms of legal protection for bank customers as consumers. 1999 concerning consumer protection, both savings agreements and credit agreements, bank customers are consumers who must obtain legal protection. Legal protection for customers should have been carried out at the pre-agreement stage until the implementation of the agreement. The issue of consumer protection is still an important issue today. Various cases of violations of consumer rights that have been going on for a long time need to be examined critically. The reason is, these violations have a very negative impact on self and consumer safety. The existence of legal protection for customers as consumers in the banking sector is urgent, because in fact the position between the parties is often unbalanced